Kesabaran sebagai nilai kebajikan dan efeknya terhadap resiliensi: Peranan moderasi dari disposisi harapan - Fahrul Rozi; Anggun Prasasti (Jurnal Psikologi Sosial, 2021)
The current study is intended to determine the role of hope in the effect of patience on resilience. This study predicts effects are impatient with the resilience reinforced with high hope disposition. 320 respondents (52% female) participated in this study with an average age of 16.3 (SD = 0.89). The results of this study indicates that hope has a significant role as a moderator in the relationship between patience and resilience. In individuals who have high disposition of hope, the effects of patience to resilience will be stronger. Meanwhile, in individuals who have lower disposition of hope, the effects of patience to resilience becomes insignificant. The results of the study prove that the effect of patience on resilience is strengthened by the high disposition of hope.